How events impact people´s mobility? A study of Lisbon´s flow patterns - Empis, Duarte Maria Bonnet Marques Patrício (2024)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence